2012
DOI: 10.1002/wsb.219
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hair cortisol concentration as a biomarker of long‐term stress in free‐ranging polar bears

Abstract: Long-term physiological stress in individual animals may be an important mechanism linking ecological change with impaired wildlife population health. In the Southern Hudson Bay (SH) subpopulation of polar bears (Ursus maritimus), increasing stress associated with climate warming may be related to declining body condition. Accordingly, the development of tools to assess long-term stress in this species may prove invaluable for conservation efforts in this threatened population. The measurement of hair cortisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 98 publications
(194 reference statements)
3
86
2
Order By: Relevance
“…Findings suggest that age has an underlying influence on benchmark cortisol levels. In polar bears, sex, size, and life-stage interactions were important factors in defining hair cortisol levels, reflecting the various influences of reproductive stress and energetic demands of growth, fasting, and migration (Macbeth et al 2012). These findings lend support to age being an important confounding variable influencing cortisol levels.…”
Section: Cortisol Associations With Biological and Biochemical Factorsmentioning
confidence: 65%
See 3 more Smart Citations
“…Findings suggest that age has an underlying influence on benchmark cortisol levels. In polar bears, sex, size, and life-stage interactions were important factors in defining hair cortisol levels, reflecting the various influences of reproductive stress and energetic demands of growth, fasting, and migration (Macbeth et al 2012). These findings lend support to age being an important confounding variable influencing cortisol levels.…”
Section: Cortisol Associations With Biological and Biochemical Factorsmentioning
confidence: 65%
“…Differences were noted between sexes only for the innermost blubber layer; however, the small sample size for females precludes a complete assessment of the influence of sex on cortisol. Results in the literature regarding sex differences in cortisol are mixed in marine and terrestrial mammals, with some documenting differences among sexes in polar bears (Oskam et al 2004;Macbeth et al 2012) whereas others found no differences in polar bears, grizzly bears, and harbour porpoises (Eskesen et al 2009;Macbeth et al 2010;Bechshoft et al 2013). The higher cortisol levels in the metabolically active inner blubber layer of females compared to males may be a reflection of higher stress conditions or energetic demands in reproductive females (Macbeth et al 2012 and references therein).…”
Section: Cortisol Levels and Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the hair growth physiology, hair vascularisation and hormone accumulation mechanisms that are associated (Koren et al, 2002;Gow et al, 2010;Stalder and Kirschbaum, 2012). No other matrix seems to have the same potential to evaluate long-term hypothalamic-pituitaryadrenal (HPA) axis activity and thereby, long-term or chronic stress (Van Uum et al, 2008;Macbeth et al, 2012;Russell et al, 2012). In spite of the clear advantages and potential applications of hair cortisol detection, several gaps need to be clarified, especially regarding the origin of the cortisol and the factors that modulate its accumulation.…”
Section: Introductionmentioning
confidence: 99%